Life-threatening arteriovenous malformation of the maxillomandibular region and treatment outcomes - A. Churojana (2018)
We report on cases of life-threatening maxillomandibular arteriovenous malformations (AVM) whereby patients had successful endovascular treatment with good outcomes. Out of a total 93 facial AVMs treated endovascularly between 1991 and 2009, five patients (5.4%) had maxillomandibular AVMs. All presented with uncontrolled dental bleeding. Endovascular procedure was the primary treatment of choice in all cases, either transfemoral approach with arterial feeder embolization or transosseous puncture, depending on the accessible route in each patient. NBCA (glue) was the only embolic agent used. Tooth extraction and dental care were performed after bleeding was controlled. All five patients (8-18 years) with a mean age of 12.4 years presented with massive dental bleeding following loosening of teeth, dental extraction and/or cheek trauma. The plain films and CT scans of four patients with AVMs of mandibles and one of maxilla, revealed expansile osteolytic lesions. The mean follow-up period was 6.6 years (ranging between one and 19 years). Three cases developed recurrent bleeding between two weeks to three months after first embolization, resulting from residual AVM and infection. Late complications occurred in two patients from chronic localized infection and osteonecrosis, which were successfully eradicated with antibiotic therapy and bony curettage. Complications occurring in two patients which included soft tissue infection, osteomyelitis and osteonecrosis were successfully treated with antibiotics, curettage and bone resection. No patient had a recurrence of bleeding after the disease had cured Initial glue embolization is recommended as the effective treatment of dental AVMs for emergent bleeding control, with the aim to complete eradicate the intraosseous venous pouches either by means of transarterial superselection or direct transosseous puncture. Patient care by a multidisciplinary team approach is important for sustained treatment results.